PENGARUH REWARD DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT GRAHA PERDANA INDAH DI SAWANGAN DEPOK - Herawati Alinda; Rima Handayani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of rewards and workload on employee performance at PT Graha Perdana Indah In Sawangan Depok partially and simultaneously. The method used is quantitative. The sampling technique uses saturated sampling, namely 89 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that rewards have a significant positive effect on employee performance with the regression equation Y = 18.747 + 0.604X1, a correlation coefficient value of 0.666 (strong positive), a determination coefficient of 44.4% and a hypothesis test obtained t count > t table or (8.334 > 1.988). Workload has a significant negative effect on employee performance with the regression equation Y = 53.609 - 0.204X2, a correlation coefficient value of -0.470 (moderate negative), a determination coefficient of 22.1% and the hypothesis test obtained t count > t table or (-4.968 > 1.988). Rewards and workload simultaneously significantly influence employee performance, with the regression equation Y = 27.747 + 0.534X1 - 0.144X2. The correlation coefficient is 0.741 (strong), with a determination coefficient of 54.9%, while the remaining 45.1% is influenced by other variables. The hypothesis test yielded a calculated F value > F table, or (52.254 > 3.100).